PENGENALAN TOKOH PAHLAWAN PADA UANG KERTAS EDISI 2014 BERBASIS AUGMENTED REALITY - Ardi Wijaya; Dinda Putri (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2021)
History lessons in Indonesia are taught starting from Elementary School (SD) level. One of materials taught in elementary schools is a national hero figure who has greatly contributed to Indonesian nation. Several images of heroes were immortalized on Indonesian banknotes. The learning method that is carried out only with printed books and lectures tends to make students bored and quickly feel sleepy. In a site like this, interesting learning media is needed. This study seeks to build an android-based application using Augmented Reality technology, using banknotes as markers to produce 3D animation applications that speak about heroes and their historical backgrounds. This application development methodology uses an Incremental model which consists of 4 stages, namely: Analysis, design, code, and testing. Distributed questionnaires get results; Strongly Disagree = 0%, Disagree = 0%, Agree = 43%, and Strongly Agree = 57%. These results indicate that the overall system is running well and feasible to use